USING AUDIO-LINGUAL METHOD TO IMPROVE THE STUDENTS’ SPEAKING SKILL - Eda Maaliah; Yulius Harry Widodo; Muhyiddin Aziz (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2017)
Language teachers play an important roles on teaching and learning process, choosing the methods, and designing the goal of the study. All their targets are based on how well they collaborate the methods and designs through the experiences and knowledge they have during the process of teaching and learning. Audio-lingual method was chosen to know the effectiveness, advantages, disadvantages, strenghts, and weaknesses in improving the speaking skill of the fifth grade students of elementary school. The qualitative and quantitative data were used in this research. Qualitative data were taken from the scores of the pre-test and all cycles. The quantitative data were taken through the observation, interview, and questionnaire. Based on the discussions and conclusions, audio-lingual method is recommended to improve the speaking skill of elementary students.Key words: audio-lingual method, speaking skill, teaching learning process